COMPONENTIAL ANALYSIS OF MEANING OF FOODS MADE OFF CASSAVA IN JAVA : SEMANTIC STUDY - Karimah, S.S, Izzati (Dinamika : Jurnal Sastra dan Budaya, 2020)
This research will discuss about the componential analysis of meaning of foods made off cassava in Java. The research method used in this study is descriptive-qualitative. In collecting the data, the researcher uses involved conversation observation continued with taking notes technique. The theory used in this research is theory of componential analysis of meaning by Nida. The result indicates that there are 22 foods made off cassava in Java namely gethuk lindri, gethuk kurung, gethuk kurung, gatot, utri, jemblem/misro, tiwul, biji salak, lemet, cenil, kue srawut/awul-awul, telo keju, klanting, slondok, keripik singkong, kerupuk opak/samiler, combro, timus, tape/peuyeum, krecek, latak, and cimplung. Cassava becomes the domain or common component. The distinctive components of foods made off cassava in Java seen from four aspects; the the mix-ingredients used, the cooking methods, the texture, and the taste of the foods. From the analysis, it can be concluded that the meaning of foods made off cassava in Java is not contained in a single meaning but there are several distinctive components that can be related it. Key words: cassava, componential analysis of meaning